The Role of Usability in Business-to-Business E-Commerce Systems: Predictors and Its Impact on User's Strain and Commercial Transactions. (30th August 2012) - Konradt, Udo; Lückel, Lüder; Ellwart, Thomas
Abstract : This study examines the impact of organizational antecedences (i.e., organizational support and information policy) and technical antecedences (i.e., subjective server response time and objective server response time) to perceived usability, perceived strain, and commercial transactions (i.e. purchases) in business-to-business (B2B) e-commerce. Data were gathered from a web-based study with 491 employees using e-procurement bookseller portals. Structural equation modeling results revealed positive relationships of organizational support and information policy, and negative relationships of subjective server response time to usability after controlling for users' age, gender, and computer experience. Perceived usability held negative relationships to perceived strain and fully mediated the relation between the three significant antecedences and perceived strain while purchases were not predicted. Results are discussed in terms of theoretical implications and consequences for successfully designing and implementing B2B e-commerce information systems.